219k views
3 votes
Solve using eliminationy = 7 - 2xy + 4x = 5Show your work here:Solution:

User Jgritten
by
6.0k points

1 Answer

3 votes

Solution


\begin{gathered} \text{ We need to rewrite the equations} \\ 2x+y=7\text{ ---------(1)} \\ 4x+y=5\text{ ---------(2)} \end{gathered}

Equation (1) - (2)


\begin{gathered} (2x-4x)+(y-y)=(7-5) \\ \\ -2x=2 \\ \Rightarrow x=(2)/(-2)=-1 \end{gathered}

2 × (1)


\begin{gathered} 2*(2x+y=7)\text{ } \\ \\ \Rightarrow4x+2y=14\text{ --------(3)} \end{gathered}

Equation (3) - (2)


\begin{gathered} (4x-4x)+(2y-y)=(14-5) \\ \\ y=9 \end{gathered}

Hence, x = -1 and y = 9

User Seanmk
by
5.6k points